TASAWUF KONTEMPLATIF: PRINSIP-PRINSIP JALAN KESUFIAN AL-MUHASIBI - Khasani, Fahim (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Al-Muhasibi's fame was unlike any other Sufi figure. he is not as popular as Al-Ghazali, even Imam Al-Junaid Al-Baghdadi. Even though both of them are students, big admirers and many are inspired by the views of Al-Muhasibi. Sufism presented by Al-Muhasibi is not an elite and exclusive science, nor is it far from irrational, eccentric and controversial. The method of Al-Muhasibi’s sufism at that time was unique. he accommodates all the knowledge that has been studied and used to develop the science of Sufism. he did not clash fiqh with tasawuf or muhaddisīn with mutakallimin, he instead integrated the four. starting from the text of the hadith which was studied by muhaddisīn and formulated into sharia law by the fuqaha, it was matured with spiritual and moral aspects by the Sufis and was written in the jadali Iqna'I style and rational dialogical style by mutakallimin. The spiritual experience (Sufism) in Al-Muhasibi’s way became a very rational conversation, not interesting in syathahāt, hulul and ittihad. The discussion related to Sufism is also not only about zuhud practices, but has been transformed into a theory and will develop into a rational scientific paradigm. Al-Muhasibi succeeded in transforming Sufism from a practical level ('Amaliy) to a theoretical level (Nadzariy) which had solid principles and foundations. he teaches us to be able to self-analyze, find bad characters and treat it, then trained to become spiritual humans by using Muhāsabah (self contemplation), riyadhah and mujahada.